Development and Evaluation of a Workshop to Support Evidence-Based Practice Change in Long-Term Care. Issue 1 (January 2015) - Higuchi, Kathryn Smith; Edwards, Nancy; Carr, Tracy; Marck, Patricia; Abdullah, Ghadah
<x xml:space="preserve">Abstract</x> To support evidence-based practice changes in long-term care, we used a practice development approach with interactive workshops to engage teams from 10 organizations in participatory change. Data from postworkshop surveys and subsequent semistructured interviews indicated that participants felt empowered to identify a priority challenge and initiate change. Notably, the workshop intervention enhanced collaboration between professional and unregulated staff, fostered the development of shared vision, and provided the impetus to tackle workplace barriers to change.